The Effect of Seed Maturity, Temperature and Storage Period on Vigor of Picrasma javanica Bl. Seedling - NINIK SETYOWATI (Biodiversitas Journal of Biological Diversity, 2009)
A study on the effect of seed maturity, temperature and period of storage on vigor of Picrasma javanica Bl. seedling was conducted at the Macropropagation Laboratory, Research Centre of Biology, LIPI, Cibinong, from March to September 2008. The research was arranged using Randomized Block Design with 3 factors and 3 replications, in which each replication had 20 samples. The first factor was stage of seed maturation with 2 levels i.e. pre-mature and mature stage; the second factor was storage temperature with 3 levels i.e. ambient temperature (28±1ºC), 20ºC and 5ºC; and the third factor was storage period with 4 levels i.e. 0, 1, 2, 3 months. The result showed that the germination time of Picrasma javanica seed was varies between 11-23 days. The mature seeds had better growth as compared to pre-mature seeds. Storage on the ambient temperature (28±1ºC) caused decrease of seed vigor, so is not suggested to seeds store in the ambient temperature. The storage under lower temperature (5ºC and 20ºC) was able to maintain seed vigor until 3 months storage.Key words: seeds maturity, temperature, storage period, vigor, Picrasma javanica Bl. seed.